Antropomorfisme dalam Taqrīrāt Jawharat al-Tawhīd: Analisis Sosiolinguistik Penafsiran KH. Maimun Zubair: Anthropomorphism in Taqrīrāt Jawharat al-Tauhīd: Sociolinguistic Analysis of KH. Maimun Zubair’s Interpretation - Ahmad Fariza Abdullah (Besari: Journal of Social and Cultural Studies, 2025)
Qur’anic interpretation has been identified with the book of tafsir (kutub al-tafāsīr), which often ignores the interpretations scattered in non-tafsir books, such as Taqrīrāt Jawharat al-Tawḥīd by KH. Maimun Zubair. Concerned with examining and analyzing his interpretation on anthropomorphism verses in that book, the researcher used a descriptive-analytical method with the conceptual framework of narrative structure analysis theory by William Labov and Joshua Waletzky. This research found that KH. Maimun Zubair strongly rejected at understanding verses that connote anthropomorphism using the tajsīm method and supported interpretation through the tafwīḍ and ta’wīl method by giving takhyīr (freedom to choose among two options). Not only being moderate and progressive, by doing so, KH. Maimun Zubair has indirectly offered the solution for taqlid problems.   Tafsir selama ini identik dengan kitab tafsir (kutub al-tafāsīr) yang seringkali mengabaikan tafsir-tafsir yang tersebar dalam kitab-kitab non tafsir, seperti Taqrīrāt Jawharat al-Tawḥīd karya KH. Maimun Zubair. Untuk mengkaji dan menganalisis tafsirnya terhadap ayat-ayat antropomorfisme dalam Taqrīrāt Jauharat al-Tauḥīd, peneliti menggunakan metode deskriptif-analitis dengan kerangka konseptual teori analisis struktur naratif oleh William Labov dan Joshua Waletzky. Penelitian ini menemukan bahwa KH. Maimun Zubair menolak keras penafsiran ayat-ayat yang mengandung makna antropomorfisme dengan metode tajsīm dan mendukung penafsiran dengan metode tafwīḍ dan ta’wīl dengan memberikan takhyīr (kebebasan memilih di antara dua pilihan). Selain bersikap moderat dan progresif, dengan demikian, KH. Maimun Zubair secara tidak langsung juga menawarkan solusi untuk masalah taqlid yang selama ini mengakar dalam masyarakat.